Functionalized Cyclopentanes via Sc(III)-Catalyzed Intramolecular Enolate Alkylation - McAtee, Christopher C. (Tetrahedron, 2018)
We report herein the intramolecular α-tert-alkylation of unsaturated β-ketoesters which gives rise to highly functionalized cyclopentanes. This strategy is characterized by its operational simplicity, mild reaction conditions and the use of scandium(III) triflate as a Lewis acid catalyst. Of interest, cyclopentanes bearing heterocycles, sites for post reaction functionalization and spirocyclic architectures are accessible with this strategy.